ماف و گرێنتیهكانی فهرمانبهران له یاساكانی ڕاژهی شارستانی عێراقید - Fathi Zero Zero; Sirwan Lateef Haji; Zangeen Maseho Adol (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The subject of the research deals with the rights and guarantees of the employees in the civil services laws, because the employees are the basis of civil services and administrative system, therefore the success or failure of the administrative activities depends on the skill of their employees and the administrative system and civil services laws. The skill of employees also depends on guaranteeing their rights, whether financial of relevant rights, regardless of guarantees which they should enjoy during their civil services laws, in order to comply with development of economic, social, technological and recent demand of employees.